2000
DOI: 10.1074/jbc.275.15.11348
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Induces Insulin-like Signaling That Antagonizes cAMP Elevation by Glucagon in Hepatocytes

Abstract: Although many effects of leptin are mediated through the central nervous system, leptin can regulate metabolism through a direct action on peripheral tissues, such as fat and liver. We show here that leptin, at physiological concentrations, acts through an intracellular signaling pathway similar to that activated by insulin in isolated primary rat hepatocytes. This pathway involves stimulation of phosphatidylinositol 3-kinase (PI3K) binding to insulin receptor substrate-1 and insulin receptor substrate-2, acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
159
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(180 citation statements)
references
References 59 publications
17
159
2
2
Order By: Relevance
“…With a specific antibody recognizing several variants of leptin receptor (15), we analyzed OBR expression at the protein level in different tissues of the TKO-OBR mice. Although this antibody has been characterized previously (15), we further demonstrated its specificity by comparing its immunoactivity with that of another leptin receptor antibody recognizing different epitopes (K20, Santa Cruz Biotechnology, CA). The results in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With a specific antibody recognizing several variants of leptin receptor (15), we analyzed OBR expression at the protein level in different tissues of the TKO-OBR mice. Although this antibody has been characterized previously (15), we further demonstrated its specificity by comparing its immunoactivity with that of another leptin receptor antibody recognizing different epitopes (K20, Santa Cruz Biotechnology, CA). The results in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The adipocytes were subsequently treated with leptin or insulin for 10 min before being harvested for analysis of leptin signaling. The analysis of PI3-kinase was carried out with a protocol described previously in which we used an anti-phosphotyrosine (pY20) antibody (Transduction Laboratory) to precipitate the PI3-kinase activity (15). The analysis of phospho-STAT3 and phospho-MAPK was based on Western blot analysis with an anti-phospho-STAT3 (pY705) antibody and an anti-phospho-MAPK (pT202/pY204) antibody, respectively (Cell Signaling).…”
Section: Fig 1 Generation Of Tko-obr Mice and Expression Of Tko-obrmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have suggested that leptin can play important physiological roles in an autocrine/paracrine way, acting in different types of cells such as adipocytes, hepatocytes, T-lymphocytes, pancreatic cells, etc. [9,10,24,28]. In fact, the role of leptin on white adipose tissue (WAT) has been reported to be essential in modulating the adipocytes' metabolic function [25], up-regulating fat oxidation [13] and decreasing lipogenesis [27].…”
Section: Introductionmentioning
confidence: 99%
“…In skeletal muscle, PKB has also been shown to be negatively regulated by cAMP and PKA signalling [21]. In hepatocytes, the ability of insulin and leptin to activate PKB was potentiated by glucagon via increases in cAMP and PKA [22]. Thus, PKB seems to be a target not only for insulin action, but also for multiple cAMP signalling pathways, resulting in an increase or decrease of its kinase activity.…”
Section: Introductionmentioning
confidence: 99%